Efeitos do corticosteroide injetado no tendão calcâneo de coelhos: análise histológica, biomecânica e das expressões de metaloproteinases e interleucinas - Dinhane, Kandir Genésio Innocenti [UNESP] (2015)
Introduction: The injection of corticosteroids (CE) for the treatment of tendinopathies is a therapeutic resource often used in orthopedic practice; however, there are clinical and experimental controversies regarding the benefits and complications of such practice. Objective: Is to evaluate the histological, biomechanical effects, and also the expression of metalloproteinases (MMP-1 and MMP-2) and interleukins (IL-1 and IL-6) on Achilles tendons of rabbits treated with CE injections. Methods: Seventy three New Zealand rabbits were randomly divided into two groups: The Test Group was comprised of thirty seven animals which underwent intratendineous injections of CE (0.2 ml of solution with 1.4 mg of betamethasone) in the Achilles tendon of the right pelvic limb, and the Control Group was comprised of thirty six animals, which provided two specimens of Achilles tendon (right and left); the Achilles tendon of the right pelvic limb underwent injections of saline solution (0.2 ml of 0.9% sodium chloride solution) and was called Placebo Control (CP); the Achilles tendon of the left pelvic limb received no medical procedure and was used as Normal Control (CN). Forty eight hours after the procedure, the animals were euthanized and the tendons were dissected and extracted at an extension of four centimeters (1.6 in) of its insertions in the calcaneus bones. The expressions of metalloproteinases and interleukins, mechanical resistance and histological analysis were all performed by an observer unaware of the groups Results: The Test Group has shown a smaller MMP-2 expression compared to those in Control Group (p= 0.027). In the Control Group, the Achilles tendon of the right pelvic limb (CP) has shown a greater amount of thick collagen fibers in comparison to those in left pelvic limb (CN) (p= 0.041). There were no other significant statistical difference between the groups when comparing other variables. Conclusions: Forty eight hours after the ...